HUBUNGAN KOMITE AUDIT DAN KOMPLEKSITAS USAHA DENGAN AUDIT FEE - Arum Ardianingsih (Jurnal Ekonomi Dan Bisnis, 2015)
The stakeholders reserve the right to get a certainty that the company activities will give them more profits. To ful fill this expectation, external auditor profession is needed. Auditor must keep their job quality like as the independency. However audit fees may cause the auditor independency is teased. The factors will be tested in this study are audit commitee and company complexity on the companies listed in BEI 2010-2012, while the sample are taken from manufacturing and mining companies. The research method used withmultiple linier regression method, with sampling techniques using purposive sampling.  The results showed that the audit committee (X1) had significant effect on audit fee (Y) with a significance level that is equal to 0,008,the company complexity (X2) had no significant effect on audit fee (Y) with a significance level that is equal to 0.578.Keywords: audit fees, audit committee, and company complexIty